Analisis Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Dana BOS - Rosdiana, Rieza (Universitas Muhammadiyah Tangerang, 2021)
This research was conducted on the school operational assistance fund (BOS) at SD Negeri Cigalasar. This study aims to determine how the accounting information system for the receipt and expenditure of BOS funds is. The object of this research is the receipt and expenditure of BOS funds. Testing is done by looking at the facts in the field regarding the acceptance of the system and also the BOS fund contest. This study uses a descriptive method with a qualitative approach. The type of data collection is by observing, documenting and interviewing the treasurer, principal, and school committee. The results of the study indicate that the accounting information system has been running well, this can be seen from the reports and evidence of each transaction, and in accordance with the applicable BOS technical guidelines.